Role of Subsidies Allocated by the Second Pillar of the Common Agricultural Policy and Diversification in Romanian Farms through Agritourism - NICOLA GALLUZZO (Romanian Review of Regional Studies, 2016)
This paper discusses about the role and the economic impact of subsidies allocated by the Common Agricultural Policy between 2007 and 2012, predominantly through the second pillar, in order to stimulate farmers to stay in the countryside and diversify their activities by agritourism. The analysis has used a quantitative approach aimed at assessing the main correlations between the growth of agritourisms and the financial supports paid by the European Union in eight Romanian administrative regions using the Farm Accountancy Data Network. Findings have pointed out that in regions where the higher has been the development of agritourism, the more significant has been the positive socio-economic impact of the funds allocated by the European Union in favour of rural development. Rural areas characterized by a low level of farmer’s income and by a high incidence of subsidies paid by the European Union in supporting rural development have brought about a considerable growth of farm diversification through agritourism. This has also corroborated the hypothesis according to which the diversification in the countryside is sensitive both to the funds allocated by the EU and to a low level of income in farms.